Serum Level Of Heat Shock Protein 70 In Patients With Polycystic Ovarian Syndrome In Iraqi Women - Ghalib, Asma; Ahmed, Taif Eimad; Yasir, Sahar Radhi; salman, Dina Akeel (Medical Science Journal for Advance Research, 2024)
Background: A common endocrine disease of fertile and postmenopausal woman was <polycystic ovarian syndromes> (PCO). Complex heterogeneous conditions, PCO has many different causes, consequences, and clinical symptoms. Uncertainty still exists regarding the pathogenic alterations of PCO. Recent study has looked into <heat shock proteins> (HSPs) functions as a cause of PCO. Therefore, the aims of the study was determine whether HSP70 serum level differ among PCO women and women as healthy control. And confirmed HSP70 can help improve PCO predictive value. MATERIALS AND METHOD: This was a case control project compose of 90 woman their age (19-42 year), 60 of them PCO diagnosed, while another 30 who are healthy control from May 2022 to November 2022. Testosterones, follicle-stimulating hormones (FSH) and Luteinizing hormones (LH) were tested by specific enzyme linked immunofluorescence assays performed in VIDAS automatic. HSP70 was tested by ELISA method based on the principle of sandwich quantification (sunlong-china). RESULT: Mean HSP70 (ng/ml) was significantly higher in women with PCO in comparison with control group (P<0.05). In addition, compared with healthy groups, hormonal biomarkers such as testosterones, LH, FSH and BMI were found to be significantly elevated in the patients. CONCLUSIONS: Increase level of the HSP70 in women with PCO showed that HSP70 plays key roles in the pathological mechanism of PCOS.